2009
DOI: 10.1111/j.1545-5300.2009.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Focused Treatment for Patients with Bipolar Disorder in Turkey: A Case Series

Abstract: Family-focused therapy (FFT) is a 9-month, 21-session structured psychoeducational treatment for bipolar disorder. Several US-based studies have documented its efficacy as adjunctive to medication for depression stabilization and relapse prevention. However, FFT has never been applied outside of the United States. The objective of this case series is to explore the applicability of FFT in a non-Western culture. Ten patients with bipolar disorder and their family members attended the 9-month FFT as adjunctive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
(33 reference statements)
0
6
0
3
Order By: Relevance
“…The 21‐session protocol required few adaptations of format or content for Turkish patients or families. The 10 study patients showed improvements in global functioning and Clinical Global Impression scale ratings over 1 year (Ozerdem, Oguz, Miklowitz, & Cimilli, ). In a nonrandomized trial involving 137 patients with BD in Italy, Fiorillo et al.…”
Section: Empirical Studies Of Fftmentioning
confidence: 99%
“…The 21‐session protocol required few adaptations of format or content for Turkish patients or families. The 10 study patients showed improvements in global functioning and Clinical Global Impression scale ratings over 1 year (Ozerdem, Oguz, Miklowitz, & Cimilli, ). In a nonrandomized trial involving 137 patients with BD in Italy, Fiorillo et al.…”
Section: Empirical Studies Of Fftmentioning
confidence: 99%
“…A critical study published in 2009 provided preliminary evidence that family‐focused therapy for bipolar disorder is acceptable to Turkish clients and may also be effective in a Turkish context. In a single group outcome study Ozerdem et al (2009) found that the approach was acceptable with minor modifications and effective in improving overall adjustment.…”
Section: Adult‐focused Problemsmentioning
confidence: 99%
“…Aile yap›s›n›n bu de¤iflimlere göre esneyebilmesi gerekir. Ülkemizde s›n›rl› mali olanaklar ve insan kaynaklar› nedeniyle yap›land›r›lm›fl aile giriflimleri çok az merkezde uygulanmakta-d›r (56). Oysa aile odakl› grup uygulamalar› flizofreni hastalar›n›n ve ailelerinin yaflam kalitelerini olumlu yönde etkileyebilir.…”
Section: Tart›flmaunclassified